Retroviral vector performance in defined chromosomal loci of modular packaging cell lines - Gama-Norton, Leonor; Herrmann, S.; Schucht, R.; Coroadinha, A. S.; Löw, R.; Alves, P. M.; Bartholomä, Cynthia C.; Schmidt, Manfred; Baum, C.; Schambach, A.; Hauser, H.; Wirth, D. (Human gene therapy, 2010)
Gamma-Norton and colleagues utilize a technology that relies on the use of packaging cell lines with predefined integration sites to evaluate the performance of several retroviral vectors. According to the authors, this approach enables the systematic design and evaluation of the efficiency and safety of retroviral vectors optimized for a given producer cell line.
Gesehen am 14.11.2023